Electrical Potential-Induced Lubricity Changes in an Ionic Liquid-Lubricated Friction Pair - Raimondas Kreivaitis; Audrius Žunda; Albinas Andriušis (Lubricants)
The control of lubricity induced by electric potential is appealing for numerous applications. On the other hand, the high polarity of ionic liquids facilitates the adsorption of equally charged molecules onto polar surfaces. This phenomenon and its consequences are well understood at the nanoscale; however, they have recently garnered significant attention at the macroscale. This study investigates the lubricity of trihexyltetradecylphosphonium dicyanamide, a phosphonium ionic liquid, when used as a neat lubricant in reciprocating sliding under electrically charged conditions. Two different polarities with the same potential were applied to the friction pair of bearing steel against bearing steel while monitoring electrical contact resistance. The lubricity was evaluated through measurements of friction, wear, surface morphology, and composition. It was found that the application of electric potential significantly alters the lubricity of the investigated ionic liquid where a positive potential applied to the ball resulted in the least damaging situation. The recorded electrical contact resistance enabled the monitoring of tribofilm formation during reciprocation. It was found that there was minimal to no separation between interacting surfaces when the ball was changing direction.